Sodium alginate fiber, preparation method thereof and reconstituted tobacco
By using sodium alginate fibers with grooved structure on the surface in the reconstructed tobacco leaves, the problem of insufficient adsorption capacity of wood pulp fibers is solved, the load rate of smoke generators and smoke release is improved, and the sensory suction quality of cigarettes is improved.
Patent Information
- Application Number
- CN202510439740.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2025-07-04
AI Technical Summary
The saturation adsorption capacity of wood pulp fibers in existing reconstructed tobacco leaves is poor, and the load rate of smoke agents is low, resulting in insufficient smoke release and heavy wood miscellaneous gases, which seriously reduces the quality of the sensory smoking of cigarettes.
Sodium alginate fiber is used to form a groove structure on its surface, and use wet spinning technology and binary solvent soaking treatment to increase the specific surface area and adsorption site of the fiber, increase the load rate of the smoke generator and lock the smoke generator, optimize the combustion characteristics and fragrance release.
It significantly improves the load rate and smoke release of smoke agents, enhances the aroma level of cigarettes, improves the sensory suction quality of cigarettes, and has good water solubility, biocompatibility and biodegradability.
Smart Images

Figure CN120250195A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of reconstituted tobacco, and particularly to a sodium alginate fiber, a preparation method thereof, and reconstituted tobacco. Background Art
[0002] Reconstituted tobacco is to process tobacco waste such as tobacco stems, broken tobacco, and tobacco dust into a kind of "artificial tobacco leaf" that can be smoked by using extraction and separation processes and papermaking techniques. This not only improves the recycling rate of tobacco materials but also reduces costs. A large amount of waste such as tobacco stems and broken tobacco leaves will be generated during the processing of tobacco leaves. Roughly calculated, reasonably utilizing these wastes and applying them to reconstituted tobacco can save hundreds of thousands of hectares of arable land in the country. This measure of "turning waste into treasure" has played a huge role in promoting the development of the domestic economy.
[0003] In the actual production process of reconstituted tobacco, in addition to using tobacco raw materials such as tobacco stems and tobacco dust, the production process of paper-making reconstituted tobacco draws on papermaking techniques and often adds wood pulp fibers, fillers, retention and drainage aids, etc. to improve the physical properties of the base paper.
[0004] Currently, the most commonly added wood pulp in reconstituted tobacco is softwood pulp and hardwood pulp. Compared with tobacco pulp fibers, wood pulp fibers are longer and have fewer fiber fragments and fines. Adding a part of wood pulp fibers has an obvious impact on the tensile strength, bulkiness, etc. of the base paper of reconstituted tobacco. However, the saturated adsorption capacity of plant fibers is poor, and the loading rate of the smoke agent is low, resulting in insufficient smoke release and heavy woody off-flavors, seriously reducing the sensory smoking quality of cigarettes. Summary of the Invention
[0005] Some embodiments of the present application provide a sodium alginate fiber, a preparation method thereof, and reconstituted tobacco, which are used to solve the problem of poor adsorption capacity of wood pulp fibers in the prior art.
[0006] In one aspect of the present application, a sodium alginate fiber is provided, and the surface of the sodium alginate fiber has a groove structure.
[0007] In some embodiments, the groove structure in the sodium alginate fiber extends along the extension direction of the sodium alginate fiber.
[0008] In some embodiments, the average diameter of the sodium alginate fiber is 20um - 40um. Optionally, the average diameter of the sodium alginate fiber is 25um.
[0009] In some embodiments, the mass water absorption multiple of the sodium alginate fiber is greater than 10.
[0010] In another aspect of the present application, there is also provided a method for preparing the above sodium alginate fiber, which includes the following steps: spinning a sodium alginate solution to obtain a nascent fiber, wherein the solvent of the sodium alginate solution includes a first solvent of the sodium alginate; soaking the nascent fiber with a binary solvent to obtain a modified fiber, the binary solvent includes a second solvent and the first solvent, and the sodium alginate has different solubilities in the first solvent and the second solvent. During the soaking process, the first solvent in the nascent fiber is replaced by the second solvent in the binary solvent; drying the modified fiber to obtain a sodium alginate fiber with a groove structure on the surface; during the drying process, the first solvent and the second solvent volatilize from the modified fiber.
[0011] In some embodiments, the volatilization rates of the first solvent and the second solvent are different.
[0012] In some embodiments, the second solvent includes one of propylene glycol, ethanol, and glycerol.
[0013] In some embodiments, the mass content of the second solvent in the binary solvent is 25% - 75%. Optionally, the mass content of the second solvent in the binary solvent is 50%.
[0014] In some embodiments, the soaking time for soaking the nascent fiber with the binary solvent is 10 min - 30 min.
[0015] In some embodiments, the first solvent includes water, and the mass ratio of sodium alginate to water is (1 - 4):100.
[0016] In some embodiments, the preparation method includes the process of preparing the sodium alginate solution, and the process of preparing the sodium alginate solution includes: stirring and mixing sodium alginate powder with water and then standing for 14 h - 16 h.
[0017] In some embodiments, during the spinning process, the rotation speed range of the spinning roller is 34 revolutions per minute to 40 revolutions per minute. Optionally, the spinning roller includes a coagulation bath roller, a stretching bath roller, a cleaning bath roller, and a collecting roller. The rotation speed of the coagulation bath roller is 34 revolutions per minute to 36 revolutions per minute, the rotation speed of the stretching bath roller is 35 revolutions per minute to 37 revolutions per minute, the rotation speed of the cleaning bath roller is 37 revolutions per minute to 39 revolutions per minute, and the rotation speed of the collecting roller is 38 revolutions per minute to 40 revolutions per minute.
[0018] In another aspect of the present application, there is also provided a reconstituted tobacco leaf, including: fibers, and the fibers include the above sodium alginate fiber.
[0019] Based on the above technical solutions, the present application has at least the following beneficial effects:
[0020] In some embodiments, the surface of the sodium alginate fiber has a groove structure, where the groove structure significantly increases the specific surface area of the fiber, provides more adsorption sites, can adsorb the smoke agent more effectively and in a larger amount, improves the smoke agent loading rate, and the groove structure helps to lock the smoke agent and reduce its volatilization loss during processing and storage; the groove structure can optimize the combustion characteristics of the reconstituted tobacco, enabling it to generate more smoke during combustion; during the suction process, the groove structure can better release the spice components, enabling the cigarette to exhibit a richer aroma level and improving the sensory suction quality of the cigarette. Description of the Drawings
[0021] The drawings described herein are used to provide a further understanding of the present application and form a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation of the present application. In the drawings:
[0022] Figure 1 This is a physical diagram of the sodium alginate fiber obtained by post-treatment with a propylene glycol solution provided in Example 1 of the present application.
[0023] Figure 2 This is an electron microscope image of the sodium alginate fiber obtained by post-treatment with a propylene glycol solution provided in Example 1 of the present application.
[0024] Figure 3 This is a water absorption multiple diagram of the sodium alginate fiber obtained by post-treatment with a propylene glycol solution provided in Example 1 of the present application.
[0025] Figure 4 This is an average elongation rate diagram of the sodium alginate fiber obtained by post-treatment with a propylene glycol solution provided in Example 1 of the present application.
[0026] Figure 5 This is an average strength diagram of the sodium alginate fiber obtained by post-treatment with a propylene glycol solution provided in Example 1 of the present application.
[0027] Figure 6 This is a physical diagram of the tobacco sheet prepared using the seaweed fiber as an additive provided in Example 1 of the present application.
[0028] It should be understood that the sizes of the various parts shown in the drawings are not drawn in actual proportional relationships. In addition, the same or similar reference numerals represent the same or similar components. Detailed Embodiments
[0029] The following further describes in detail the embodiments of the present application in conjunction with the examples. The detailed descriptions of the following examples are used to exemplarily illustrate the principles of the present application, but cannot be used to limit the scope of the present application, that is, the present application is not limited to the described examples.
[0030] As analyzed in the background art of this application, the wood pulp fibers added in the preparation process of reconstituted tobacco in the prior art have poor saturated adsorption capacity and low loading rate of the smoke agent, resulting in insufficient smoke release and heavy woody off-flavors, seriously reducing the sensory smoking quality of cigarettes. Based on this, this application provides a sodium alginate fiber, a preparation method thereof, and reconstituted tobacco. The sodium alginate fiber provided by this application has good water solubility, biocompatibility, and biodegradability. The surface of the sodium alginate fiber has a groove structure, which can improve the adsorption capacity, increase the loading rate of the smoke agent and the smoke release amount, and improve the sensory smoking quality of cigarettes, and can solve the problems of heavy woody off-flavors, poor saturated adsorption capacity of plant fibers, low loading rate of the smoke agent, and insufficient smoke release amount.
[0031] In a typical embodiment of this application, a sodium alginate fiber is provided, and the surface of the sodium alginate fiber has a groove structure.
[0032] The surface of the sodium alginate fiber provided in the embodiment of this application has a groove structure, in which the groove structure significantly increases the specific surface area of the fiber, provides more adsorption sites, can adsorb the smoke agent more effectively and in a larger amount, increases the loading rate of the smoke agent, and the groove structure helps to lock the smoke agent and reduce its volatilization loss during processing and storage; the groove structure can optimize the combustion characteristics of the reconstituted tobacco, making it produce more smoke during combustion; during the smoking process, the groove structure can better release the spice components, making the cigarette exhibit a richer aroma level and improving the sensory smoking quality of the cigarette.
[0033] In some embodiments, the groove structure in the sodium alginate fiber extends along the extension direction of the sodium alginate fiber.
[0034] In the above embodiment, the groove structure extends along the extension direction of the sodium alginate fiber, which can enable the smoke agent, spices, and other additives to be adsorbed onto the fiber more evenly and efficiently along the extension direction of the sodium alginate fiber, thereby improving the adsorption efficiency of the fiber, increasing the loading rate of the smoke agent, etc., and improving the overall sensory experience.
[0035] In some embodiments, the average diameter of the sodium alginate fiber is 20um to 40um. Optionally, the average diameter of the sodium alginate fiber is 25um.
[0036] In the above embodiments, the length of the sodium alginate fiber can range from a few millimeters to several meters, and the average diameter of the sodium alginate fiber is 20 μm to 40 μm, approximately around 25 μm. The sodium alginate fiber with a smaller diameter has a higher specific surface area, which can increase the intermolecular interaction, thereby improving the strength and toughness of the fiber. Moreover, due to its larger specific surface area, the fiber with a smaller diameter can provide more adsorption sites, so it has better moisture absorption and moisture retention capabilities, improving the loading rate of the smoke agent and the smoke release amount, and enhancing the sensory smoking quality of the cigarette.
[0037] The sodium alginate fiber provided by this application with the above length and average diameter has excellent strength and toughness, excellent adsorption properties, and excellent water solubility, biocompatibility, and biodegradability.
[0038] In some embodiments, the mass water absorption multiple of the sodium alginate fiber is greater than 10.
[0039] In the above embodiments, the ratio of the mass of the sodium alginate fiber after water absorption to its mass when dry is greater than 10. Therefore, the mass water absorption multiple of the sodium alginate fiber is greater than 10. The sodium alginate fiber provided by this application can adsorb the smoke agent more effectively and in a larger amount, improving the loading rate of the smoke agent.
[0040] The sodium alginate fiber provided by this application has good mechanical strength and acid and alkali resistance, and has the advantages of simple preparation, low cost, and environmental friendliness.
[0041] In another typical embodiment of this application, a preparation method for preparing the above sodium alginate fiber is also provided, which includes the following steps: spinning the sodium alginate solution to obtain a primary fiber, and the solvent of the sodium alginate solution includes a first solvent for sodium alginate; soaking the primary fiber with a binary solvent to obtain a modified fiber; the binary solvent includes a second solvent and the first solvent, and sodium alginate has different solubilities in the first solvent and the second solvent. During the soaking process, the first solvent in the primary fiber is replaced by the second solvent in the binary solvent; drying the modified fiber to obtain a sodium alginate fiber with a groove structure on the surface; wherein during the drying process, the first solvent and the second solvent volatilize from the modified fiber.
[0042] The above preparation method immerses the nascent fiber in a binary solvent. When the nascent fiber is immersed in the binary solvent, due to the different concentrations of the first solvent in the nascent fiber and the first solvent in the binary solvent, there is a concentration difference, which causes the first solvent in the nascent fiber to diffuse into the binary solvent. Since there is no second solvent in the nascent fiber, and the concentration of the second solvent in the nascent fiber is different from that of the second solvent in the binary solvent, there is a concentration difference, which causes the second solvent in the binary solvent to diffuse into the nascent fiber, resulting in a replacement effect between the first solvent in the nascent fiber structure and the second solvent in the binary solvent, forming a modified fiber; also, because sodium alginate has different solubilities in the first solvent and the second solvent, it causes a certain offset aggregation of the polymer chains in the modified fiber structure; at the same time, during the subsequent drying process, the first solvent and the second solvent volatilize from the modified fiber, generating a further phase separation effect, thereby forming a groove structure on the surface of the sodium alginate fiber. The groove structure significantly increases the specific surface area of the fiber, provides more adsorption sites, can adsorb the smoke agent more effectively and in greater quantity, improves the smoke agent loading rate, and the groove structure helps to lock the smoke agent and reduce its volatilization loss during processing and storage; the groove structure can optimize the combustion characteristics of the reconstituted tobacco, making it produce more smoke during combustion; during the suction process, the groove structure can better release the fragrance components, making the cigarette exhibit a richer aroma level and improving the sensory suction quality of the cigarette.
[0043] In some embodiments, the first solvent and the second solvent have different volatilization rates.
[0044] In the above embodiments, the first solvent and the second solvent have different boiling points and thus different volatilization rates. Therefore, the first solvent and the second solvent separate from the modified fiber at different speeds, generating a further phase separation effect, thereby making it easier to form a groove structure on the surface of the sodium alginate fiber and further improving the adsorption and smoke loading rate of the sodium alginate fiber.
[0045] In some embodiments, the concentration of the first solvent in the nascent fiber reaches 100%, and the concentration of the second solvent in the nascent fiber is 0%.
[0046] In some embodiments, the volume of the binary solvent is more than three times the volume of the nascent fiber, but not limited thereto, as long as it is ensured that during the process of immersing the nascent fiber in the binary solvent, the second solvent in the binary solvent can fully replace the first solvent in the nascent fiber.
[0047] In some embodiments, the second solvent is a poor solvent for sodium alginate.
[0048] In some embodiments, the second solvent includes one of propylene glycol, ethanol, and glycerol.
[0049] In the above embodiments, the second solvent of the binary solvent is propylene glycol, the first solvent is water, and the evaporation rate of propylene glycol is less than that of water; or, the second solvent in the binary solvent is ethanol, the first solvent is water, and the evaporation rate of ethanol is greater than that of water; or, the second solvent in the binary solvent is glycerol, the first solvent is water, and the evaporation rate of glycerol is less than that of water.
[0050] In the above embodiments, propylene glycol, ethanol, and glycerol are all organic solvents containing hydroxyl groups and can hardly dissolve sodium alginate.
[0051] In the above embodiments, since the concentration of the first solvent in the primary fiber (100%) is greater than the concentration of the first solvent in the binary solvent, the first solvent in the primary fiber diffuses into the binary solvent. Since the concentration of the second solvent in the primary fiber (0%) is less than the concentration of the second solvent in the binary solvent, the second solvent in the binary solvent diffuses into the primary fiber, causing a displacement effect between the first solvent in the primary fiber structure and the second solvent in the binary solvent. That is, the hydroxyl group-containing solvent will replace water, turning the primary fiber into a modified fiber. During the drying process, the first solvent and the second solvent in the modified fiber evaporate successively, and the sodium alginate fiber dehydrates and shrinks, forming an oriented groove structure along the fiber stretching direction after drying. Therefore, a groove structure can be formed on the surface of the sodium alginate fiber.
[0052] In some embodiments, the mass content of the second solvent in the binary solvent is 25% - 75%. Optionally, the mass content of the second solvent in the binary solvent is 50%.
[0053] In the above embodiments, if the mass content of the second solvent in the binary solvent is too low, it cannot fully displace the first solvent in the primary fiber. If the mass content of the second solvent in the binary solvent is too high, the second solvent will remain in the dried fiber. Therefore, the mass content of the second solvent in the binary solvent is 25% - 75%, which can not only achieve full displacement with the first solvent in the primary fiber but also avoid the residue of the second solvent in the dried sodium alginate fiber.
[0054] In some embodiments, the mass content of propylene glycol in the binary solvent can be 25% - 75%; or, the mass content of ethanol in the binary solvent is 25% - 75%; or, the mass content of glycerol in the binary solvent is 25% - 75%.
[0055] In some embodiments, the primary fiber is immersed in a binary solvent with a mass content of the second solvent of 25%. Or, the primary fiber is immersed in a binary solvent with a mass content of the second solvent of 50%. Or, the primary fiber is immersed in a binary solvent with a mass content of the second solvent of 75%.
[0056] In some embodiments, the immersion time of the nascent fiber in the binary solvent is 10 min to 30 min. Optionally, the immersion time of the nascent fiber in the binary solvent is 15 min to 25 min.
[0057] In some embodiments, the immersion time of the nascent fiber in the binary solvent is 10 min, 20 min or 30 min.
[0058] In the above embodiments, if the immersion time of the nascent fiber in the binary solvent is too short, the replacement of the first solvent in the nascent fiber by the second solvent in the binary solvent is limited, and the fibers are likely to adhere after drying; if the immersion time of the nascent fiber in the binary solvent is too long, there is too much residue of the second solvent, and the fibers are difficult to dry. Therefore, by using the immersion time within the above range, the second solvent in the binary solvent can effectively replace the first solvent in the nascent fiber, and the excessive residue of the second solvent in the sodium alginate fiber can be avoided.
[0059] In some embodiments, the second solvent in the binary solvent is propylene glycol, and the mass content of propylene glycol in the binary solvent is 25% to 75%. The nascent fiber is immersed in the binary solvent for 10 min to 30 min to obtain a modified fiber, and the modified fiber is dried to obtain a sodium alginate fiber with a groove structure on the surface.
[0060] In the above embodiments, the second solvent is propylene glycol. The sodium alginate fiber obtained by post-treatment with a propylene glycol solution is subjected to acid and alkali resistance tests. It is experimentally measured that it does not decompose after being immersed in an acid and alkali solution with a pH of 2 to 10 for 3 days, and its acid and alkali resistance performance is good; the tensile strength of the sodium alginate fiber is tested, and it is experimentally measured that its strength is greater than 1.2 cN / dtex, even greater than 1.68 cN / dtex, and the elongation rate is greater than 14%, even greater than 17.25%; the water absorption rate of the sodium alginate fiber is tested, and it is experimentally measured that its mass water absorption multiple is greater than 10 times, and its water absorption rate is excellent.
[0061] In some embodiments, the second solvent in the binary solvent is ethanol or glycerol, and the mass content of ethanol or glycerol in the binary solvent is 40% to 60%. The nascent fiber is immersed in the binary solvent for 10 min to 30 min to obtain a modified fiber, and the modified fiber is dried to obtain a sodium alginate fiber with a groove structure on the surface.
[0062] In the above embodiments, the second solvent is glycerol. The primary fiber is soaked in a binary solvent with a glycerol mass content of 40% - 60%, and after drying, sodium alginate fibers with a groove structure on the surface are obtained. The acid and alkali resistance of the sodium alginate fibers is tested. The experiment measures that they do not decompose after being soaked in acid and alkali solutions with pH = 2 - 10 for 3 days, and their acid and alkali resistance performance is good; the tensile strength of the sodium alginate fibers is tested, and the experiment measures that their strength > 0.98 cN / dtex and elongation rate > 15%; the water absorption rate of the sodium alginate fibers is tested, and the experiment measures that their water absorption multiple is greater than 10 times, and the water absorption rate is excellent.
[0063] In the above embodiments, the second solvent is ethanol. The primary fiber is soaked in a binary solvent with an ethanol mass content of 40% - 60%, and after drying, sodium alginate fibers with a groove structure on the surface are obtained. The acid and alkali resistance of the sodium alginate fibers is tested. The experiment measures that they do not decompose after being soaked in acid and alkali solutions with pH = 2 - 10 for 3 days, and their acid and alkali resistance performance is good; the tensile strength of the sodium alginate fibers is tested, and the experiment measures that their strength > 1.4 cN / dtex and elongation rate > 12%; the water absorption rate of the sodium alginate fibers is tested, and the experiment measures that their water absorption multiple is greater than 10 times, and the water absorption rate is excellent.
[0064] In some embodiments, the first solvent includes water, and the mass ratio of sodium alginate to water is (1 - 4) : 100.
[0065] In the above embodiments, the sodium alginate solution is the spinning dope. If the concentration of the spinning dope is higher, the time required for dissolution and defoaming is longer, and the viscosity is too high, resulting in poor fluidity and being not conducive to spinning; if the concentration of the spinning dope is too low, the formed primary fiber is extremely easy to break and difficult to draw. Therefore, using the above numerical range for the mass ratio of sodium alginate to water can not only avoid the too high viscosity of the spinning dope being not conducive to spinning, but also improve the strength of the primary fiber and be conducive to drawing.
[0066] In some embodiments, the sodium alginate powder is one of food grade or food additive grade.
[0067] In some embodiments, the preparation method includes the process of preparing the sodium alginate solution, and the process of preparing the sodium alginate solution includes: stirring and mixing the sodium alginate powder with water and then standing for 14h - 16h.
[0068] In the above embodiments, if the standing time after stirring and mixing the sodium alginate powder with water is too short, the defoaming effect will be reduced, and thus the spinning quality will be affected by the residual bubbles in the solution; if the standing time after stirring and mixing the sodium alginate powder with water is too long, the spinning efficiency will be reduced. Using the above standing time is beneficial to improving the defoaming effect and the spinning efficiency.
[0069] In some embodiments, during the spinning process, the rotational speed range of the spinning roller is 34 revolutions per minute to 40 revolutions per minute. Optionally, the spinning roller includes a coagulation bath roller, a drawing bath roller, a cleaning bath roller, and a collecting roller. Among them, the rotational speed of the coagulation bath roller is 34 revolutions per minute to 36 revolutions per minute, the rotational speed of the drawing bath roller is 35 revolutions per minute to 37 revolutions per minute, the rotational speed of the cleaning bath roller is 37 revolutions per minute to 39 revolutions per minute, and the rotational speed of the collecting roller is 38 revolutions per minute to 40 revolutions per minute.
[0070] In the above embodiments, the drawing process can improve the fiber toughness and is beneficial to fiber forming, but too low a rate is not conducive to the improvement of fiber strength; therefore, when setting the drawing speed in this application, within the above rotational speed range, the speed of the coagulation bath roller can be adjusted slower, and the speed of the drawing bath roller can be adjusted faster, so that both the soaking time of the fiber in the coagulation bath can be ensured to be longer and the fiber can be fully drawn, and then high-orientation primary fibers can be obtained after being washed with pure water.
[0071] In some embodiments, the preparation method for preparing the above sodium alginate fiber includes the following steps: adopting the wet spinning technology, pouring a sodium alginate solution with a certain mass concentration into a spinning kettle, standing for defoaming, and obtaining high-orientation primary fibers by using tensile traction; soaking the primary fibers in a binary solvent to displace the first solvent in the primary fibers with the second solvent in the binary solvent to obtain modified fibers; drying the modified fibers in an oven to prepare a high-liquid-absorbing sodium alginate fiber with a groove structure for reconstituted tobacco leaves.
[0072] The sodium alginate fiber prepared by the preparation method provided in this application has good tensile strength (1.68 cN / dtex) and acid and alkali resistance (insoluble in acid and alkali solutions with pH = 2 to 10), and has the characteristics of simple preparation, low preparation cost, environmental friendliness, and good liquid absorption performance (the mass water absorption multiple is greater than 10 times). When applied in composite tobacco sheets (reconstituted tobacco leaves), it can improve the liquid absorption capacity and loading rate, increase the smoke release amount of the sheets, solve problems such as low loading amount and small fog amount existing in traditional sheets, and improve the sensory suction quality of heated cigarettes.
[0073] In some embodiments, the preparation method for preparing the above sodium alginate fiber includes the following steps:
[0074] (1) Mix sodium alginate powder and pure water in a mass ratio of (1 to 4):100, stir at room temperature or under heating conditions until completely dissolved to form a sodium alginate solution, that is, the spinning dope, and pour the spinning dope into a spinning kettle and stand for defoaming for 14 h to 16 h.
[0075] (2) Using the wet spinning technology, spin the spinning dope; wherein, according to the fiber stretching direction, set the rotation speeds of the four rollers of the spinning machine to 34 revolutions per minute to 40 revolutions per minute, optimize the stretching traction force and the fiber crosslinking strength, and then wash the fiber with pure water to obtain highly oriented nascent fibers.
[0076] (3) Immerse the nascent fibers obtained in step (2) in a binary solvent with the mass content of the second solvent being 25% to 75% for 10 min to 30 min, so that the first solvent in the nascent fibers is replaced by the second solvent in the binary solvent to obtain modified fibers, and dry the modified fibers. The second solvent and the first solvent in the modified fibers volatilize successively, thereby preparing a highly absorbent sodium alginate fiber for reconstituted tobacco with a groove structure.
[0077] The method for preparing a tobacco sheet using sodium alginate fiber as an additive includes: mixing the highly absorbent seaweed fiber obtained in step (3) with tobacco stem pulp, coating and drying to make a sample to obtain a composite heated tobacco sheet, and this sheet exhibits excellent liquid absorption performance with a water absorption rate > 53 mm / 10 min.
[0078] In another typical embodiment of the present application, a reconstituted tobacco is provided, which includes fibers, and the fibers include the above-mentioned sodium alginate fibers.
[0079] The technical principle for preparing sodium alginate fiber in the present application is as follows: using the wet spinning technology to prepare nascent fibers from sodium alginate solution, immersing the nascent fibers in a binary solvent to make the first solvent in the nascent fibers be replaced by the second solvent in the binary solvent to obtain modified fibers; drying the modified fibers in an oven to prepare a highly absorbent sodium alginate fiber for reconstituted tobacco with a groove structure, and applying the capillary core absorption principle of this groove structure and the formed ultra-large specific surface area to reconstituted tobacco.
[0080] The present application uses the green, low-carbon and environmentally friendly wet spinning technology, binary solvent post-treatment technology, etc. to prepare a highly absorbent sodium alginate fiber for reconstituted tobacco with a groove structure on the surface, which can promote the rapid and large absorption of the smoke generator and the coating liquid on the tobacco sheet, improve the loading amount and quality stability of the smoke generator on the tobacco sheet, increase the smoke release amount of the tobacco sheet, solve the problems such as low loading amount and small fog amount existing in traditional tobacco sheets, and improve the sensory suction quality of heated cigarettes.
[0081] The beneficial effects of the present application will be further described below in combination with examples and comparative examples, but the scope of the present invention is not limited to these examples.
[0082] Example 1
[0083] (1) Mix sodium alginate powder with pure water at a mass ratio of 3:100, stir at room temperature or under heating conditions until completely dissolved to form a sodium alginate solution, which is the spinning dope. Pour the spinning dope into a spinning kettle and let it stand for 16 h (hours) to defoam. Among them, the first solvent of sodium alginate is pure water;
[0084] (2) Using wet spinning technology, spin the spinning dope. According to the fiber stretching direction, set the rotation speeds of the four rollers of the spinning machine to 34 revolutions per minute, 36 revolutions per minute, 38 revolutions per minute, and 40 revolutions per minute in sequence to optimize the stretching traction force and fiber cross-linking strength, obtain fibers, and then wash the fibers with pure water to obtain highly oriented primary fibers;
[0085] (3) Immerse the primary fibers obtained in step (2) in a binary solvent with a mass content of propylene glycol (PG, Propylene Glycol) of 25% - 75% for 20 min to displace the water in the primary fibers with propylene glycol in the binary solvent to obtain modified fibers. Dry the modified fibers in an oven to prepare highly absorbent sodium alginate fibers (post-treated fibers) with a groove structure on the surface for reconstituted tobacco.
[0086] The method for preparing tobacco sheets using sodium alginate fibers as additives includes: mixing the highly absorbent sodium alginate fibers obtained in step (3) with tobacco stem pulp, coating and drying to make a sample to obtain composite heated tobacco sheets.
[0087] In Example 1, three binary solvents with different mass contents of propylene glycol can be selected to immerse the primary fibers respectively to obtain three kinds of sodium alginate fibers. For example: select a binary solvent with a mass content of propylene glycol of 75% to immerse the primary fibers, select a binary solvent with a mass content of propylene glycol of 50% to immerse the primary fibers, and then select a binary solvent with a mass content of propylene glycol of 25% to immerse the primary fibers to obtain three kinds of sodium alginate fibers.
[0088] Reference Figures 1 to 5 , for Example 1, the physical diagram, electron microscope diagram and performance diagram of the fibers obtained by post-treatment after immersing the primary fibers in a binary solvent using propylene glycol as the second solvent.
[0089] As Figure 1 shown, it is the physical diagram of the fibers prepared by immersing the primary fibers in a propylene glycol solution. In the figure, the fibers are distinct from each other, with excellent fiber gloss and flexibility.
[0090] As Figure 2 shown, it is the electron microscope diagram of the fibers prepared by immersing the primary fibers in a propylene glycol solution. The fibers have an obvious "groove" structure, which increases their water absorption area and can absorb more water.
[0091] AsFigure 3 As shown in the figure, the water absorption multiple diagrams of three kinds of fibers prepared by immersing nascent fibers in binary solvents with three mass contents of propylene glycol (25%, 50%, 75%) are presented. It can be seen that when propylene glycol is used as the binary solvent, the higher the mass content of propylene glycol, the higher the average mass water absorption multiple of the sodium alginate fibers after post-treatment. It is speculated that this is because propylene glycol has a water retention effect. The higher the content of propylene glycol, the more propylene glycol remains in the sodium alginate fibers during post-treatment, and the more water is adsorbed.
[0092] As Figure 4 shown in the figure, the average elongation rate diagrams of the fibers prepared by immersing nascent fibers in binary solvents with three mass contents of propylene glycol (25%, 50%, 75%) are presented. It can be seen that when propylene glycol is used as the binary solvent, the higher the mass content of propylene glycol, the higher the average elongation rate of the sodium alginate fibers after post-treatment.
[0093] As Figure 5 shown in the figure, the average strength diagrams of the fibers prepared by immersing nascent fibers in binary solvents with three mass contents of propylene glycol (25%, 50%, 75%) are presented. It can be seen that when propylene glycol is used as the binary solvent, the higher the mass content of propylene glycol, the higher the average strength of the sodium alginate fibers after post-treatment.
[0094] As Figure 6 shown in the figure, the physical diagram of the cigarette sheet prepared by using sodium alginate fibers as additives.
[0095] For Example 1, the acid and alkali resistance test was carried out on the post-treated fibers obtained in step (3). The experiment measured that they did not decompose after being immersed in acid and alkali solutions with pH = 2 - 10 for 3 days, indicating good acid and alkali resistance. The tensile strength test was carried out on the post-treated fibers obtained in step (3). The experiment measured that their strength was 1.68 cN / dtex and the elongation rate was 17.25%. The water absorption rate test was carried out on the post-treated fibers obtained in step (3). The experiment measured that their mass water absorption multiple was greater than 10 times, indicating excellent water absorption rate.
[0096] For Example 1, the liquid absorption rate test was carried out on the cigarette sheet prepared by using sodium alginate fibers as additives. The results showed that the sheet exhibited excellent liquid absorption performance, and the water absorption rate > 53 mm / 10 min.
[0097] Example 2:
[0098] (1) Mix sodium alginate powder and pure water in a mass ratio of 1:100, stir at room temperature or under heating conditions until completely dissolved to form a sodium alginate solution, that is, the spinning dope. Pour the spinning dope into the spinning kettle and let it stand for defoaming for 16 h; among them, the first solvent of sodium alginate is pure water;
[0099] (2) Using the wet spinning technique, spin the spinning dope; according to the fiber stretching direction, set the rotational speeds of the four rollers of the spinning machine to 34 revolutions per minute, 36 revolutions per minute, 38 revolutions per minute, and 40 revolutions per minute in sequence, optimize the stretching traction force and the fiber crosslinking strength, obtain fibers, and then obtain highly oriented primary fibers after washing the fibers with pure water;
[0100] (3) Immerse the primary fibers obtained in step (2) in a binary solvent with a mass content of propylene glycol of 25% - 75% for 20 min to displace the first solvent in the primary fibers with the second solvent in the binary solvent, obtaining modified fibers; dry the modified fibers in an oven to prepare highly absorbent sodium alginate fibers (post-treated fibers) with a groove structure on the surface for reconstituted tobacco.
[0101] The method for preparing tobacco sheets using sodium alginate fibers as additives includes: mixing the highly absorbent sodium alginate fibers obtained in step (3) with tobacco stem pulp, coating and drying to make a sample, and obtaining composite heated tobacco sheets.
[0102] For Example 2, perform acid and alkali resistance tests on the post-treated fibers obtained in step (3). The experiment measures that they do not decompose after being immersed in different acid and alkali solutions (pH = 2 - 10) for 3 days, showing good acid and alkali resistance. Perform tensile strength tests on the post-treated fibers obtained in step (3). The experiment measures that their strength is 1.2 cN / dtex and the elongation at break is 14%. Perform water absorption rate tests on the post-treated fibers obtained in step (3). The experiment measures that their mass water absorption multiple is greater than 10 times, showing excellent water absorption rate.
[0103] For Example 2, perform liquid absorption rate tests on the tobacco sheets prepared using sodium alginate fibers as additives. The results show that the sheets exhibit excellent liquid absorption performance, with a water absorption rate > 50 mm / 10 min.
[0104] Example 3:
[0105] (1) Mix sodium alginate powder and pure water in a mass ratio of 3:100, stir at room temperature or under heating conditions until completely dissolved to form a sodium alginate solution, which is the spinning dope, and pour the spinning dope into a spinning kettle and let it stand for defoaming for 16 h; wherein, the first solvent of sodium alginate is pure water;
[0106] (2) Using the wet spinning technique, spin the spinning dope; according to the fiber stretching direction, set the rotational speeds of the four rollers of the spinning machine at 34 revolutions per minute, 36 revolutions per minute, 38 revolutions per minute, and 40 revolutions per minute in sequence, optimize the stretching traction force and the fiber crosslinking strength, obtain fibers, and then obtain highly oriented primary fibers after washing the fibers with pure water;
[0107] (3) Immerse the as - spun fibers obtained in step (2) in a binary solvent with a propylene glycol mass content of 25% - 75% for 30 min to displace the first solvent in the as - spun fibers with the second solvent in the binary solvent, obtaining modified fibers; dry the modified fibers in an oven to prepare a highly absorbent sodium alginate fiber for reconstituted tobacco with a grooved structure on the surface.
[0108] The method for preparing tobacco sheets using sodium alginate fibers as additives includes: mixing the highly absorbent sodium alginate fibers obtained in step (3) with tobacco stem pulp, coating, drying and sampling to obtain composite heated cigarette sheets.
[0109] For Example 3, perform acid - base resistance tests on the post - treated fibers obtained in step (3). It is experimentally measured that they do not decompose after being immersed in acid - base solutions with pH = 2 - 10 for 3 days, indicating good acid - base resistance performance. Perform tensile strength tests on the post - treated fibers obtained in step (3). It is experimentally measured that their strength > 1.02 cN / dtex and elongation rate > 13%. Perform water absorption tests on the post - treated fibers obtained in step (3). It is experimentally measured that their mass water absorption multiple is greater than 10 times, indicating excellent water absorption.
[0110] For Example 3, perform liquid absorption rate tests on the tobacco sheets prepared using sodium alginate fibers as additives. The results show that the sheets exhibit excellent liquid absorption performance, with a liquid absorption rate > 50 mm / 10 min.
[0111] Example 4:
[0112] (1) Mix sodium alginate powder and pure water in a mass ratio of 3:100, stir at room temperature or under heating conditions until completely dissolved to form a sodium alginate solution, which is the spinning dope. Pour the spinning dope into a spinning kettle and let it stand for defoaming for 16 h (hours); wherein, the first solvent of sodium alginate is pure water.
[0113] (2) Use wet spinning technology to spin the spinning dope; according to the fiber stretching direction, set the rotation speeds of the four rollers of the spinning machine to 34 revolutions per minute, 36 revolutions per minute, 38 revolutions per minute, and 40 revolutions per minute in sequence to optimize the stretching traction force and fiber cross - linking strength, obtaining fibers. Wash the fibers with pure water to obtain highly oriented as - spun fibers.
[0114] (3) Immerse the as - spun fibers obtained in step (2) in a binary solvent with a glycerol mass content of 50% for 20 min to displace the first solvent in the as - spun fibers with the second solvent in the binary solvent, obtaining modified fibers; dry the modified fibers in an oven to prepare a highly absorbent sodium alginate fiber for reconstituted tobacco with a grooved structure on the surface.
[0115] The method for preparing tobacco sheet using sodium alginate fiber as an additive includes: mixing the highly absorbent seaweed fiber obtained in step (3) with tobacco stem pulp, and subjecting the mixture to coating and drying to prepare a sample, thereby obtaining a composite heated cigarette sheet.
[0116] For Example 4, the post-treatment fiber obtained in step (3) was subjected to acid and alkali resistance tests. It was experimentally measured that it did not decompose after being immersed in an acid-base solution with a pH of 2 to 10 for 3 days, indicating good acid and alkali resistance performance. The post-treatment fiber obtained in step (3) was subjected to a tensile strength test. It was experimentally measured that its strength > 0.98 cN / dtex and its elongation rate > 15%. The post-treatment fiber obtained in step (3) was subjected to a water absorption rate test. It was experimentally measured that its mass water absorption multiple was greater than 10 times, indicating excellent water absorption rate.
[0117] For Example 4, the tobacco sheet prepared using sodium alginate fiber as an additive was subjected to a liquid absorption rate test. The results showed that the sheet exhibited excellent liquid absorption performance, with a water absorption rate > 46 mm / 10 min.
[0118] Example 5:
[0119] (1) Mix sodium alginate powder with pure water at a mass ratio of 3:100, and stir at room temperature or under heating conditions until completely dissolved to form a sodium alginate solution, which is the spinning dope. Pour the spinning dope into a spinning kettle and let it stand for defoaming for 16 h (hours); wherein, the first solvent of sodium alginate is pure water;
[0120] (2) Using the wet spinning technique, spin the spinning dope; according to the fiber stretching direction, set the rotation speeds of the four rollers of the spinning machine to 34 revolutions per minute, 36 revolutions per minute, 38 revolutions per minute, and 40 revolutions per minute in sequence to optimize the stretching traction force and fiber crosslinking strength, thereby obtaining fibers. The fibers were then washed with pure water to obtain highly oriented primary fibers;
[0121] (3) Immerse the primary fibers obtained in step (2) in a binary solvent with an ethanol mass content of 50% for 20 min to displace the first solvent in the primary fibers with the second solvent in the binary solvent, thereby obtaining modified fibers; dry the modified fibers in an oven to prepare highly absorbent sodium alginate fibers for reconstituted tobacco with a groove structure on the surface.
[0122] The method for preparing tobacco sheet using sodium alginate fiber as an additive includes: mixing the highly absorbent seaweed fiber obtained in step (3) with tobacco stem pulp, and subjecting the mixture to coating and drying to prepare a sample, thereby obtaining a composite heated cigarette sheet.
[0123] For Example 5, the post-treated fibers obtained in step (3) were subjected to acid and alkali resistance tests. It was experimentally measured that they did not decompose after being immersed in acid and alkali solutions with a pH of 2 to 10 for 3 days, indicating good acid and alkali resistance. The post-treated fibers obtained in step (3) were subjected to tensile strength tests. It was experimentally measured that their strength was > 1.4 cN / dtex and the elongation at break was > 12%. The post-treated fibers obtained in step (3) were subjected to water absorption tests. It was experimentally measured that their mass water absorption multiple was greater than 10 times, indicating excellent water absorption.
[0124] For Example 5, the liquid absorption rate of the tobacco sheet prepared using sodium alginate fiber as an additive was tested. The results showed that the sheet exhibited excellent liquid absorption performance, with a water absorption rate > 46 mm / 10 min.
[0125] Comparative Example 1:
[0126] (1) Sodium alginate powder was mixed with pure water at a mass ratio of 3:100 and stirred at room temperature or under heating until completely dissolved to form a sodium alginate solution, which is the spinning dope. The spinning dope was poured into a spinning kettle and left to stand for defoaming for 16 h (hours); among them, the first solvent of sodium alginate was pure water;
[0127] (2) Using the wet spinning technology, the spinning dope was spun; according to the fiber stretching direction, the rotation speeds of the four rollers of the spinning machine were set to 34 revolutions per minute, 36 revolutions per minute, 38 revolutions per minute, and 40 revolutions per minute in sequence to optimize the stretching traction force and fiber cross-linking strength to obtain fibers. The fibers were then washed with pure water to obtain highly oriented primary fibers;
[0128] (3) After drying the primary fibers obtained in step (2), the fibers shrank severely and had poor gloss.
[0129] The post-treated fibers obtained in step (3) of Comparative Example 1 were subjected to acid and alkali resistance tests. It was experimentally measured that they did not decompose after being immersed in acid and alkali solutions with a pH of 2 to 10 for 3 days, indicating good acid and alkali resistance. The post-treated fibers obtained in step (2) were subjected to tensile strength tests. It was experimentally measured that their strength was too poor. The post-treated fibers obtained in step (2) were subjected to water absorption tests. It was experimentally measured that their water absorption multiple was too small.
[0130] From Comparative Example 1, it can be seen that the soaking process in the binary solvent is very important. When the primary fibers are soaked in the binary solvent, the second solvent in the binary solvent will displace the water in the primary fibers, and the fibers will dehydrate and shrink, forming an oriented groove structure along the fiber stretching direction after drying. Without the soaking process in the binary solvent, no groove structure will be generated.
[0131] Comparative Example 2:
[0132] (1) Mix sodium alginate powder and pure water in a mass ratio of 5:100, stir at room temperature or under heating conditions until completely dissolved to form a sodium alginate solution, which is the spinning dope. Pour the spinning dope into a spinning kettle and let it stand for defoaming for 16 h (hours). Among them, the first solvent of sodium alginate is pure water;
[0133] (2) Use wet spinning technology to spin the spinning dope. According to the fiber stretching direction, set the rotation speeds of the four rollers of the spinning machine to 34 revolutions per minute, 36 revolutions per minute, 38 revolutions per minute, and 40 revolutions per minute in sequence to optimize the stretching traction force and fiber cross-linking strength, obtain fibers, and then wash the fibers with pure water to obtain highly oriented primary fibers;
[0134] (3) Immerse the primary fibers obtained in step (2) in a binary solvent with a mass content of propylene glycol of 25% - 75% for 30 min to displace the first solvent in the primary fibers with the second solvent in the binary solvent to obtain modified fibers. After drying the modified fibers, post-treated fibers are obtained.
[0135] Perform acid and alkali resistance tests on the post-treated fibers obtained in step (3) of Comparative Example 2. It is experimentally measured that they do not decompose after being immersed in acid and alkali solutions with a pH of 2 - 10 for 3 d, and the acid and alkali resistance performance is good. Perform tensile strength tests on the post-treated fibers obtained in step (3). It is experimentally measured that their strength is too poor. Perform water absorption tests on the post-treated fibers obtained in step (3). It is experimentally measured that their water absorption multiple is too small.
[0136] According to Comparative Example 2: When the mass ratio of sodium alginate powder to pure water is 5:100, the solution is too viscous, it is not easy to remove bubbles, the fibers are not easy to stretch, cannot form filaments, and are easy to break.
[0137] Comparative Example 3:
[0138] (1) Mix sodium alginate powder and pure water in a mass ratio of 3:100, stir at room temperature or under heating conditions until completely dissolved to form a sodium alginate solution, which is the spinning dope. Pour the spinning dope into a spinning kettle and let it stand for defoaming for 16 h (hours). Among them, the first solvent of sodium alginate is pure water;
[0139] (2) Use wet spinning technology to spin the spinning dope. According to the fiber stretching direction, set the rotation speeds of the four rollers of the spinning machine to 34 revolutions per minute, 36 revolutions per minute, 38 revolutions per minute, and 40 revolutions per minute in sequence to optimize the stretching traction force and fiber cross-linking strength, obtain fibers, and then wash the fibers with pure water to obtain highly oriented primary fibers;
[0140] (3) Immerse the as - spun fibers obtained in step (2) in a binary solvent with a mass content of propylene glycol of 25% - 75% for 5 min to replace the first solvent in the as - spun fibers with the second solvent in the binary solvent, obtaining modified fibers; after drying the modified fibers, post - treated fibers are obtained.
[0141] Perform acid and alkali resistance tests on the post - treated fibers obtained in step (3) of Comparative Example 3. The experiment measures that they do not decompose after being immersed in acid - base solutions with pH = 2 - 10 for 3 days, showing good acid and alkali resistance. Perform tensile strength tests on the post - treated fibers obtained in step (3). The experiment measures that their strength is too poor. Perform water absorption rate tests on the post - treated fibers obtained in step (3). The experiment measures that their water absorption multiple is too small.
[0142] According to Comparative Example 3: The soaking time of the as - spun fibers in the binary solvent is too short, and the replacement of water by propylene glycol in the binary solvent is limited. After drying, the fibers are prone to adhesion. If the soaking time of the as - spun fibers in the binary solvent is too long, too much propylene glycol remains, and the fibers are difficult to dry.
[0143] According to the above - mentioned various embodiments and comparative examples, the present application has at least the following beneficial effects:
[0144] The preparation method of the present application has a simple process and is universal, applicable to sodium alginate solutions with different concentrations. The strength of the high - liquid - absorbing sodium alginate fibers prepared is greater than 1.68 cN, and the elongation rate is greater than 17.25%, which can meet the actual application requirements of reconstituted tobacco leaves.
[0145] The present application can prepare sodium alginate fibers with a groove structure on the surface by adjusting the concentration of the spinning dope and the rotational speed of different rollers, which can improve the mass water absorption multiple (>10) and acid and alkali resistance (insoluble at pH = 2 - 10) of the sodium alginate fibers.
[0146] The high - liquid - absorbing sodium alginate fibers prepared by the present application can replace plant fibers and be applied to reconstituted tobacco leaves, solving problems such as relatively heavy woody off - flavors of plant fibers, poor saturated adsorption capacity, low loading rate of the fumigant, and insufficient smoke release.
[0147] Based on the above - mentioned embodiments of the present application, without explicit negation or conflict, the technical features of one embodiment can be beneficially combined with one or more other embodiments.
[0148] Although some specific embodiments of the present application have been described in detail by way of examples, those skilled in the art should understand that the above examples are only for illustration purposes and not for limiting the scope of the present application. Those skilled in the art should understand that the above embodiments can be modified or equivalent substitutions can be made for some technical features without departing from the scope and spirit of the present application. The scope of the present application is defined by the appended claims.
Claims
1. A sodium alginate fiber, wherein the surface of the sodium alginate fiber has a groove structure.
2. The sodium alginate fiber according to claim 1, wherein The groove structure in the sodium alginate fiber extends along the extension direction of the sodium alginate fiber.
3. The sodium alginate fiber according to claim 1 or 2, characterized in that, The average diameter of the sodium alginate fiber is 20um - 40um. Optionally, the average diameter of the sodium alginate fiber is 25um.
4. The sodium alginate fiber according to any one of claims 1 to 3, characterized in that The mass water absorption multiple of the sodium alginate fiber is greater than 10.
5. A preparation method for preparing the sodium alginate fiber according to any one of claims 1 to 4, which comprises the following steps: Spinning the sodium alginate solution to obtain a primary fiber, wherein the solvent of the sodium alginate solution comprises a first solvent of the sodium alginate; Soaking the primary fiber with a binary solvent to obtain a modified fiber, the binary solvent comprises a second solvent and the first solvent, and the sodium alginate has different solubilities in the first solvent and the second solvent. During the soaking process, the first solvent in the primary fiber is replaced by the second solvent in the binary solvent; Drying the modified fiber to obtain a sodium alginate fiber with a groove structure on the surface; during the drying process, the first solvent and the second solvent volatilize from the modified fiber.
6. The preparation method according to claim 5, characterized in that, The volatilization rates of the first solvent and the second solvent are different.
7. The preparation method according to claim 5 or 6, characterized in that, The second solvent comprises one of propylene glycol, ethanol, and glycerol.
8. The preparation method according to any one of claims 5 to 7, characterized in that, The mass content of the second solvent in the binary solvent is 25% - 75%. Optionally, the mass content of the second solvent in the binary solvent is 50%.
9. The preparation method according to any one of claims 5 to 8, characterized in that, The soaking time for soaking the primary fiber with the binary solvent is 10min - 30min.
10. The preparation method according to any one of claims 5 to 9, characterized in that, The first solvent comprises water, and the mass ratio of the sodium alginate to water is (1 - 4):
100.
11. The preparation method according to any one of claims 5 to 10, characterized in that, The preparation method includes the process of preparing the sodium alginate solution, and the process of preparing the sodium alginate solution includes: Stirring and mixing the sodium alginate powder with water and then standing for 14h - 16h.
12. The preparation method according to any one of claims 5 to 11, characterized in that, During the spinning process, the rotation speed range of the spinning roller is 34 revolutions per minute - 40 revolutions per minute. Optionally, the spinning roller includes a coagulation bath roller, a stretching bath roller, a cleaning bath roller, and a collecting roller. The rotation speed of the coagulation bath roller is 34 revolutions per minute - 36 revolutions per minute, the rotation speed of the stretching bath roller is 35 revolutions per minute - 37 revolutions per minute, the rotation speed of the cleaning bath roller is 37 revolutions per minute - 39 revolutions per minute, and the rotation speed of the collecting roller is 38 revolutions per minute - 40 revolutions per minute.
13. A reconstituted tobacco leaf, comprising fibers, characterized in that, The fiber includes the sodium alginate fiber according to any one of claims 1 to 4.